1974
DOI: 10.1159/000251489
|View full text |Cite
|
Sign up to set email alerts
|

Sweet’s Syndrome

Abstract: A case of Sweet’s syndrome (acute febrile neutrophilic dermatosis) is reported. The occurrence of systemic disorders in other reported cases is discussed. Extensive immunological studies in this case have failed to reveal any underlying abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Nunji (12), Tsuchiya (8) and Matsubara (13), in their immunopathological studies, found igG, IgM and IgE-bearing polymorphonuclear leucocytes in the involved skin of patients with Sweet's syndrome. Mackie (14) found IgD in affected skin and postulated this as proof of vasculitis (15), but it is not always characteristic of Sweet's syndrome.…”
mentioning
confidence: 99%
“…Nunji (12), Tsuchiya (8) and Matsubara (13), in their immunopathological studies, found igG, IgM and IgE-bearing polymorphonuclear leucocytes in the involved skin of patients with Sweet's syndrome. Mackie (14) found IgD in affected skin and postulated this as proof of vasculitis (15), but it is not always characteristic of Sweet's syndrome.…”
mentioning
confidence: 99%